Diskursus Tasawuf Nusantara di Mekah: Respons Mukhtār ‘Aṭārid Al-Bughūrī terhadap Ajaran Martabat Tujuh - Jajang A. Rohmana (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2021)
This study focuses on the discourse of Malay-Indonesian Sufism in Mecca at the beginning of the twentieth century. My main object is the response of Mukhtār ‘Aṭārid of Bogor (1862-1930) towards the doctrine of seven grades using the social history approach. He is a Sundanese scholar who taught in Mecca. He gave the response in his two Sundanese printed kitabs in Egypt. The study shows that Mukhtār’s response reflects the importance of Sunni orthodoxy on Sufism based on sharia. Therefore, he tends to reject the deviation of the seven grades teachings in the Indonesian archipelago which considered deviant. In the case of the teaching of Ibn ‘Arabi’s unity of existence, Mukhtār' Aṭārid seems to correct people’s misunderstandings about this teaching. He advised to be good-minded to the teaching because Ibn ‘Arabi is an expert of truth in accordance with the sharia, but most people are not able to understand it. The view point of Mukhtār ‘Atārid reflects the response of a scholar who heir to the tradition of Sunni Sufism orthodoxy towards the development of Sufism in Indonesian archipelago that spread out from the seventeenth century to the present. Keywords: seven grades, Sufism, Sunni, Sundanese Kajian ini memfokuskan pada masalah wacana tasawuf Nusantara di Mekah pada awal abad ke-20. Objek utamanya adalah tanggapan Mukhtār ‘Aṭārid al-Bughūrī (1862-1930), ulama Sunda yang mengajar di Mekah, terhadap konsep martabat tujuh. Ia menuangkannya dalam dua kitab berbahasa Sunda yang dicetak di Mesir, Kifāyah al-Mubtadi’īn dan Hidāyah al-Mubtadi’in. Melalui pendekatan sejarah sosial, hasil kajian menunjukkan bahwa tanggapan Mukhtār ‘Aṭārid mencerminkan kepentingan ortodoksi Sunni dalam bidang tasawuf yang bertumpu pada syariat. Karenanya, ia cenderung menolak penyimpangan ajaran martabat tujuh di Nusantara yang dianggapnya heterodoks dan menyimpang. Sementara dalam kasus ajaran kesatuan eksistensi (tauḥīd al-wujūd) Ibn ‘Arabī, al-Jilī dan al-Burhānfūrī, Mukhtār ‘Aṭārid terlihat meluruskan kesalahpahaman orang terhadap ajarannya itu. Ia menganjurkan untuk berbaik sangka pada ajarannya, karena diyakini merupakan ahli hakikat yang benar dan sesuai dengan syariat, tetapi kebanyakan orang tidak mampu memahaminya. Pandangan Mukhtār ‘Aṭārid mencerminkan respons seorang ulama pewaris tradisi ortodoksi sufistik Sunni terhadap perkembangan tasawuf di Nusantara yang membentang sejak abad ke-17 hingga sekarang. Kata kunci: martabat tujuh, tasawuf, Sunni, bahasa Sunda